Optimalisasi Motivasi Dan Kinerja Guru Dengan Pendekatan Faktor Motivator Dan Hygiene Di MIN 1 Kota Bandung - Zulfa, Amanah Amnun; Nugraha, Mulyawan Safwandy (El-Idare, 2024)
This study aims to explore ways to enhance teacher motivation and performance at Madrasah Ibtidaiyah Negeri (MIN) 1 Bandung, focusing on the application of motivator and hygiene factors based on Herzberg's two-factor theory. The research identifies key elements such as appreciation, responsibility, and opportunities for self-development as motivators, while aspects like fair policies, adequate facilities, and positive relationships among teachers are considered hygiene factors. The study employs a descriptive qualitative method, utilizing interviews, observations, and document analysis with teachers and the head of the madrasah. The findings indicate that MIN 1 Bandung has adequately addressed both types of factors to improve teacher motivation and performance. The combination of motivator and hygiene factors has proven effective in boosting teacher commitment and enthusiasm, especially when aligned with Islamic values. Motivator factors contribute to enhancing intrinsic satisfaction and commitment, whereas hygiene factors help reduce dissatisfaction and create a stable work environment. These findings support the principles of educational psychology, which emphasize the importance of meeting educators' psychological needs to ensure optimal teaching quality.